The SIESTA geographic database : instruction for its use and maintenance - Krabbe, W.K. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2021)
102 pág, ilus, tab, 4 ref.